PENGARUH HUBUNGAN GERAKAN PENERAPAN PENGELOLAAN TANAMAN TERPADU (GP-PTT) DENGAN PENINGKATAN PRODUKSI TANAMAN KEDELAI - Zulkarnain, Zulkarnain (Politeknik Negeri Lampung., 2016)
Food crops sector as producers of staple food for the people of Indonesia, so that this role can not be substituted fully by other sectors except food imports.Soybean crop is one of the staple food for the people of Indonesia that demand is increasing, therefore the government held a movement program Implementation of Integrated Crop Management (GP-PTT) to increase soybean production. The purpose of this study was to analyze the effect of the relationship Movement Implementation of Integrated Crop Management (GP-PTT) in the increased production of soybeans in Rejo village Binangun Raman District of North East Lampung district. The method used is a qualitative and quantitative methods. The sample was 27 farmers were taken by systematic random sampling technic. Data analysis method used is the analysis method validity, reliability, and Spearman rank test. This research was conducted in the village of Rejo Binangun Raman District of North East Lampung district in April 2016. The results showed that the the factors related to business assistance in relation Movement Application Processing Integrated Plant (GP-PTT) with an increase in the production of soybean on variable business assistance, PPT technology component, group participation. The third variable business assistance, the variable component PPT technology, variable group participation are of marked meaning if the higher aid farming, technology components, and group participation, the interest of farmers for the higher soybean. Keyword: Integrated Crop Management, Production, Soybean Plant